Laryngeal reconstruction using autologous rib cartilage and T stent – a case report - Warmus, Janusz; Gil, Tomasz; Gocyk, Wojciech; Ziętkiewicz, Mirosław; Kużdżał, Jarosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
We present a case of surgical treatment of traumatic laryngeal injury with loss of about half its circumference. Stage therapy was applied. The primary reconstruction was to restore the front of the larynx with the help of autologous rib cartilage, supporting with the silicone T-tube stent. Complement treatment was lower tracheostomy. The next steps include endoscopic therapy, during which shortened the length of the stent and granulation tissue removed. After 6 months, the T-tube stent was removed, obtaining recovery.